Penayangan Film Secara Live Streaming Tanpa Izin - Gusti Kadek Bagaskara; Sutrisno . (Widya Yuridika, 2022)
This research aims to give an understanding about the regulation of the action of showing movies in live streaming without permission based on Act No. 28 of 2014 about  Copyright. This research uses normative juridical method and analytical descriptive in processing the data with the qualitative approach to determine the content and the meaning of the law regulation in order to be the reference in resolving legal problems that has been the object of the study. The result of this research concludes that the action of showing movies without permission based on Act No. 28 of 2014 about Copyright in Article 9 Paragraph 3 which is every action of showing movies in live streaming without any permission violated the article. The violation in the copyright cases violates two rights of the copyright owner of the creation which are moral rights and economic rights of the creator or the copyright owner. With the rise of the amount of platforms in doing live streaming there are so many misuse that has been done. Most of cases that happen often are not handled further.This is because of some factors such as the media that is too broad and the lack of supervision. Other than that, there are so many parties do not understand about the copyright violation because it is considered as a normal act. In some cases, the violator knew that their act violated the law but they consciously still do that because there is no penalty or further action for their crime from the authorities.